Some aspects regarding the use of a pneumomechanical high speed forming process - Akst, O.; Djakow, E.; Homberg, W. (Technische Universität Dortmund, 2012)
A promising approach to the production of thin-walled workpieces in high strength materials is the use of a special pneumomechanical high-speed-forming process. This process uses a pneumatically accelerated plunger that dives into a pressure chamber filled with the working media in order to generate a short pressure pulse. Ways in which the pressure pulse can be influenced include e.g. varying the type of working media, the density of the working media, the accelerating pressure distance and the plunger geometry. The influence of these parameters on the process formed the subject of intense technological research at the Chair of Forming and Machining Technology (LUF) at Paderborn University. The results of these investigations were used to achieve an appropriate process and tool design for the pneumomechanical high-speed forming process. It thus proved possible to manufacture complex workpieces and geometrical details from thin-walled, high strength stainless steel or aluminium alloys that cannot be produced by conventional stamping processes. Because of the high uniformity of the pressure distribution in the radial direction, it is possible to achieve just small dimensional or geometrical deviations in respect of the desired shape of the workpiece. The planned paper will present results of the basic research conducted into pneumomechanical high-speed-forming as well as a comparison with electrohydraulic forming.
Keywords: electro hydraulic forming; high speed hydroforming; pneumomechanical forming; 620; 670